Entrepreneurship Learning and Social Environment: The Determinants that Appear Entrepreneurial Interest for Students - Andi Naila Quin Azisah Alisyahbana; Andika Isma; Bakry Bakry (Pinisi Journal of Entrepreneurship Review, 2023)
This study aims to determine the determinants of student entrepreneurial interest as seen from entrepreneurship learning and social environment. This study examines partially and simultaneously the effect of student entrepreneurial interest in entrepreneurship study programs at Universitas Negeri Makassar. This research is categorized as quantitative descriptive research with a population of 401 entrepreneurship students at Universitas Negeri Makassar class of 2019-2021. Data obtained through the distribution of questionnaires with a Likert scale. The analysis technique used is descriptive statistical analysis, analysis of prerequisite analysis, hypothesis testing and determination coefficient test. The results of this study indicate that entrepreneurship learning and social environment partially and simultaneously have a significant effect on entrepreneurial interest in entrepreneurship students of Universitas Negeri Makassar. This means that entrepreneurship learning and the social environment are determinants of the emergence of entrepreneurial interest for students of entrepreneurship study programs at public universities in Makassar.